Putusan Hakim Dalam Penjatuhan Pidana Pembayaran Uang Pengganti (Studi Kasus Pengadilan Tipikor Semarang) - Anna Thresia Silitonga, Pujiyono, Sukinta (Diponegoro Law Journal, 2012)
Corruption is a crime that can undermine the values ​​of democracy and morality, because it acts slowly as a culture. Where in the case of corruption found many problems une of them on payment of compensation under the provosions of Law No. 31 of 1999 Jo. Law No. 20 of 2001, judge legal considerations, constraints judge in the imposition of criminal and efforts to overcome it. The research method used in the writing of this law is a normative juridical approach, an emphasis on the study of jurisprudence, beginning with an analysis of the law governing the Corruption, especially in the chapters relating to the payment of compensation issues. Besides normative juridical approach also uses empirical juridical approach is a method by studying the constraints faced by the Judge in the case of criminal punishment for compensation and seek ways to overcome these obstacles. From the results of research by the author, or the results obtained the conclusion that if the guilty party does not pay the compensation that should be his property seized by prosecutors and auctioned off to cover the compensation. Before the judge impose additional criminal, he must first be able to see the criminal elements in the Article 18 of Law No. 31 of 1999 Jo. Law No. 20 of 2001. In addition, the judges must see first whether the defendant enjoys the results of his alleged corruption. If it is not proven that he can not be imposed additional punishment. So the judges do not experience problems because judges in deciding its properties here just to use the Act only.